Pendidikan Islam pada Zaman Modern Sultan Mahmud II - I’anatul Ashriyah; Abdul Khobir (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This article explains Islamic education during the time of Sultan Mahmud II in 1808-1839 in the Ottoman Empire. Sultan Mahmud II is known for his reform policies which had an impact on various sectors, including education. In the context of Islamic education, he seeks to update the curriculum, teaching methods and structure of educational institutions to respond to the challenges of the developing modern era, both in political, social and cultural contexts. The aim of this research is to find out about Islamic education during the time of Sultan Mahmud II. The method used in this research is library research, namely research that obtains data using reading results from literature such as books, journal articles and other reading materials. The results of the research and discussion of this article show that the education carried out by Sultan Mahmud II was focused on renewing Islamic education by incorporating general knowledge into the educational curriculum. Sultan Mahmud II also founded public schools, such as Maktebi Ma'arif and Maktebi Ulum'i Edibiyet, as well as medical, military, and engineering schools. Islamic education in modern times is experiencing an important transition, although it remains based on strong Islamic religious values.